The role of political uncertainty in Australian financial markets - Smales, Lee (Wiley-Blackwell Publishing Asia, 2015)
Within the developed world, recent Australian political history is uniquely turbulent. This situation invokes indecision regarding investment decisions in both the real economy and the financial markets. This paper explores the relationship between uncertainty in Australian federal election polling and resulting financial market uncertainty. Empirical evidence suggests that increasing (decreasing) levels of uncertainty around the election result induce higher (lower) levels of uncertainty in financial markets. The effect is more pronounced as polling day approaches. Industry-level analysis suggests that the base materials sector is most significantly affected by election uncertainty in Australia